2018
DOI: 10.1158/0008-5472.can-17-0946
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in Protein Tyrosine Phosphatase PTP1B Shortens Lifespan and Leads to Development of Acute Leukemia

Abstract: Protein tyrosine phosphatase PTP1B is a critical regulator of signaling pathways controlling metabolic homeostasis, cell proliferation, and immunity. In this study, we report that global or myeloid-specific deficiency of PTP1B in mice decreases lifespan. We demonstrate that myeloid-specific deficiency of PTP1B is sufficient to promote the development of acute myeloid leukemia. LysM-PTP1B mice lacking PTP1B in the innate myeloid cell lineage displayed a dysregulation of bone marrow cells with a rapid decline in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 48 publications
1
32
1
Order By: Relevance
“…Indeed, PTP1B inhibition using antisense oligonucleotides enhances insulin sensitivity and decreases weight in T2D patients [ 14 ]. However, it is worth noting that myeloid-specific PTP1B deficiency in mice leads to the development of acute leukemia [ 72 ], suggesting the need for a targeted inhibitor delivery. Indeed, intracerebroventricular administration of a small-molecule PTPB inhibitor prevents binge drinking-induced systemic insulin resistance and glucose intolerance [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PTP1B inhibition using antisense oligonucleotides enhances insulin sensitivity and decreases weight in T2D patients [ 14 ]. However, it is worth noting that myeloid-specific PTP1B deficiency in mice leads to the development of acute leukemia [ 72 ], suggesting the need for a targeted inhibitor delivery. Indeed, intracerebroventricular administration of a small-molecule PTPB inhibitor prevents binge drinking-induced systemic insulin resistance and glucose intolerance [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Work form several groups has demonstrated that protein tyrosine phosphatases play a relevant role in the process of macrophage polarization acting, not only as negative regulators of pro-inflammatory signaling, but also as attenuators of anti-inflammatory pathways [21] , [33] , [34] , [35] , [36] , [37] . Moreover, in addition to immune regulation, an essential role for PTP1B in obesity-induced chronic low-grade inflammation and in other pathologies including diabetes, cancer, neuroinflammation, liver diseases or Rett syndrome, has been described as evidenced by the use of selective PTP1B inhibitors or animal models targeted for PTP1B [12] , [18] , [20] , [22] , [38] , [39] , [40] , [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PTP1B seems to be a relevant target in the protection against ionizing radiation. Indeed, absence of PTP1B reduces life-span and enhances the appearance of lymphoproliferative disorders in mice [18] . Also, these results are in agreement with previous data on the role of myeloid cell irradiation (macrophages among them) in oncogenic treatments [42] , [43] , [44] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic reprogramming also has a significant impact on the progression, treatment and prognosis of AML (10,11). More precisely, there are abnormalities in the metabolic processes of AML such as glycolysis, amino acid metabolism, fatty acid metabolism, epigenetic modification and autophagy pathway (12).…”
Section: Introductionmentioning
confidence: 99%